Effects of modifier (Gd, Sc, La) addition on the stability of low Ni content catalyst for dry reforming of model biogas. (15th March 2022) - Ha, Quan Luu Manh; Atia, Hanan; Kreyenschulte, Carsten; Lund, Henrik; Bartling, Stephan; Lisak, Grzegorz; Wohlrab, Sebastian; Armbruster, Udo
Graphical abstract: Highlights: Gd, La and Sc improve stability of low Ni content Al2 O3 -MgO catalysts in DRM. Rare earth elements stabilize Ni dispersion and promote CO2 activation. Gd sufficiently establishes both effects. Outstanding stability in excess methane (CH4 /CO2  = 2) at 630 and 750 °C. Successful exceptional long-term tests over 100 h at high space velocity. Abstract: Biogas consists of a larger part of methane and a smaller part of carbon dioxide. Reforming biogas is highly desirable due to the direct conversion of the two components, yet not possible due to the current state of catalyst development. For such dry reforming of methane-rich gases (CH4 /CO2  = 2) we now present catalysts with low Ni loading (2.5 wt%) modified with Gd, Sc, or La. The best catalyst reaches 49% CH4 conversion and 95% CO2 conversion at 750 °C. The La-modification only shows limited influence on coking and protection against catalyst deactivation although this catalyst exposed highest basicity. On the other side, Sc- and especially Gd-modified catalysts exposed stronger metal-support interaction and thus enhanced stabilization of fine Ni particles during the reaction, which is critical to preserve high performance in CH4 -rich DRM. This suppressed carbon deposition and the growth of structured carbon as evidenced by STEM images and TPO of spent catalysts. In this way, exceptionally high specific H2 productivity (94 l/(gcat ·h)) compared to literature was obtained on Gd-modified catalyst, and, most noteworthy, after extending the time on stream from 8 to 100 h the amount of deposited coke increased only from 3 to 4 wt%.